Gradient fully synthetic engine oil filter material and preparation method thereof

Through the design of gradient fully synthesized engine oil filter material and the composite of polyester fiber spunbond non-woven fabric, the existing engine oil filter paper has solved the shortcomings in heat-resistant oil aging and high precision, and achieved long life and high-efficiency filtration effects, satisfying the high-end Customer needs.

CN116510422BActive Publication Date: 2025-01-03SHANDONG RENFENG SPECIAL MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310407466.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-17
Publication Date
2025-01-03
Estimated Expiration
2043-04-17

AI Technical Summary

Technical Problem

The existing engine oil filter paper cannot meet the needs of high-end customers for long life, especially under the requirements of 150,000 Km+ heat-resistant oil aging, the combination method of traditional wood pulp fiber and synthetic fiber is insufficient.

Method used

Gradient fully synthesized engine oil filter material is used to gradient composite by using polyester fibers with different precision and dirt absorption capabilities on the oil inlet, oil outlet and intermediate layer respectively, and composite polyester fibers spunbond non-sold on the oil outlet surface The adhesive coating technology of acrylic resin glue and PVA glue is achieved with low resistance and high efficiency filtration effect.

Benefits of technology

It has achieved a long-life and high-precision engine oil filter paper, which can meet the aging ability of heat-resistant oil over 2000h, and achieve the performance indicators of 20μm filtration efficiency >90% and dirt absorption capacity >180g/m².

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention discloses a gradient fully synthetic oil filter material and a preparation method thereof, and belongs to the technical field of oil filter paper. The present invention performs gradient compounding on a three-layer structure with low quantitative and different precision and dirt holding capacity, and at the same time compounds a polyester material on the fully synthetic material on the oil outlet surface, and can directly perform origami and hot plate welding processes, thus truly realizing a fully synthetic oil filter material with long life, high precision, low resistance and high efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of engine oil filter paper, and in particular to a gradient fully synthetic engine oil filter material and a preparation method thereof. Background Art

[0002] Oil filter paper is the key material of oil filter, and the normal working temperature of oil filter is 110℃-150℃. At present, the mainstream oil filter paper at home and abroad is still made of wood pulp fiber and synthetic fiber as the main raw materials. However, with the long life demand of high-end customers for oil filter paper, this raw material combination can no longer meet the 150,000 km+ heat oil aging requirements. Therefore, it is necessary to keep up with the needs of the main engine manufacturers and develop oil filter paper that can meet the long life requirements. Summary of the invention

[0003] The technical problem to be solved by the present invention is: to overcome the shortcomings of the prior art, to provide a gradient fully synthetic engine oil filter material and a preparation method thereof, to gradiently compound a three-layer structure with low quantitative different precisions and dirt holding capacities, and at the same time to compound a polyester material on the fully synthetic material on the oil outlet surface, and to directly perform origami and hot plate welding processes, to truly realize a fully synthetic engine oil filter material with long life, high precision, low resistance and high efficiency.

[0004] The technical solution of the present invention is:

[0005] The preparation method of the gradient fully synthetic oil filter material comprises the following steps:

[0006] Preparation of S1 oil inlet surface fully synthetic material

[0007] S11 pulping: first disperse 1.5D polyester fiber and 3D polyester fiber, then disperse the skin-core structure two-component polyester fiber, and finally disperse the glass fiber;

[0008] S12 Internet access forming;

[0009] S13 Gluing: Use acrylic resin glue and PVA glue for dipping glue;

[0010] S14 drying: drying the semi-finished product after glue coating to obtain the oil-filled fully synthetic material;

[0011] The fully synthetic material of the oil inlet surface mainly provides dust holding capacity, so the paper sheet is required to be thick and bulky. The 3D and 1.5D polyester fibers have appropriate coarseness and can provide higher air permeability and bulk. If only one of the polyester fibers is used, the air permeability will be too high or too low, which will not meet the design requirements.

[0012] Preparation of S2 middle layer fully synthetic material

[0013] S21 pulping: first disperse 67D polyester fiber, then disperse the skin-core structure two-component polyester fiber, and finally disperse the glass fiber;

[0014] S22 online forming;

[0015] S23 Gluing: Use acrylic resin glue and PVA glue for surface coating;

[0016] S24 drying: drying the semi-finished product after gluing to obtain the middle layer fully synthetic material;

[0017] Preparation of S3 oil outlet surface fully synthetic material

[0018] S31 pulping: first disperse 0.3D polyester fiber and 1.5D polyester fiber, then disperse the skin-core structure two-component polyester fiber, and finally disperse the glass fiber;

[0019] S32 online forming;

[0020] S33 Gluing: Use acrylic resin glue for dipping;

[0021] S34 Drying: Drying the semi-finished product after gluing to obtain the oil surface full synthetic material;

[0022] The oil inlet surface fully synthetic material, the middle layer fully synthetic material and the oil outlet surface fully synthetic material are compounded, and after compounding, the polyester fiber spunbond non-woven fabric is compounded on the oil outlet surface fully synthetic material.

[0023] During the preparation process, the dispersion order of each fiber is limited because: 1) it is determined by the final dispersion state, and the fibers that are more difficult to disperse in the ratio are dispersed first, and then the fibers that are easier to disperse are dispersed to obtain a uniformly dispersed slurry; 2) it is determined by the length of the fiber. The pulping time affects the length structure of the fiber. According to the designed target air permeability and bulk or performance standards, the pulping order is designed to avoid the fibers that provide bulk performance from being cut off due to being fed first, resulting in bulk and air permeability not meeting the design requirements.

[0024] The present invention adopts a bicomponent polyester fiber with a core-skin structure, which can produce a self-adhesive effect when the paper sheet is dried. The core layer provides higher physical and mechanical properties and heat resistance, and the skin layer provides good adhesiveness, thereby improving the strength of a single-layer paper.

[0025] When preparing the fully synthetic material for the oil inlet surface and the fully synthetic material for the middle layer, acrylic resin glue and PVA glue are used for coating, while acrylic resin glue is used for coating the fully synthetic material for the oil outlet surface. This is because the oil inlet and outlet surfaces need to meet the strength requirements of the product and be able to withstand the pressure during use. PVA glue can provide better strength, but because it has a greater impact on air permeability and a certain impact on oil resistance, PVA glue and acrylic emulsion should be used simultaneously on the oil inlet surface and the middle layer to ensure sufficient air permeability while achieving better strength.

[0026] Preferably, in step S11, pulping includes the following raw materials in parts by weight: 50-62 parts of 3D polyester fiber, 12-19 parts of 1.5D polyester fiber, 12-18 parts of bicomponent polyester fiber with a core-sheath structure and 1.5-3 parts of glass fiber, and the beating degree is greater than 40°SR; in step S21, pulping includes the following raw materials in parts by weight: 61-70 parts of 67D polyester fiber, 8-15 parts of bicomponent polyester fiber with a core-sheath structure and 3-5.5 parts of glass fiber, and the beating degree is greater than 35°SR; in step S31, pulping includes the following raw materials in parts by weight: 65-77 parts of 0.3D polyester fiber, 10-17 parts of 1.5D polyester fiber, 5-7 parts of bicomponent polyester fiber with a core-sheath structure and 5-7.5 parts of glass fiber, and the beating degree is greater than 50°SR.

[0027] Preferably, in steps S11, S21 and S31, the dispersion process is carried out in a hydraulic pulper; in step S11, the mass concentration of the fiber in water is 7-12%, in step S21, the mass concentration of the fiber in water is 1.2%-1.5%, and in step S31, the mass concentration of the fiber in water is 0.5-1%.

[0028] Preferably, in step S11, the dispersion time of 1.5D polyester fiber and 3D polyester fiber is 5-7 min, the dispersion time of sheath-core bicomponent polyester fiber is 2-4 min, and the dispersion time of glass fiber is 8-11 min; in step 21, the dispersion time of 0.67D polyester fiber is 4-6 min, the dispersion time of sheath-core bicomponent polyester fiber is 2-4 min, and the dispersion time of glass fiber is 10-12 min; in step S31, the dispersion time of 0.3D polyester fiber and 1.5D polyester fiber is 6-7 min, the dispersion time of sheath-core bicomponent polyester fiber is 1-3 min, and the dispersion time of glass fiber is 15-17 min.

[0029] Preferably, in steps S11, S21 and S31, after dispersion, the slurry is uniformly passed through a high-frequency deflaking machine without knife adjustment; then the slurry enters a slurry mixing tank and a dispersant is added, wherein in steps S11 and S21, 0.1‰ of dispersant is added, and in step S31, 0.3‰ of dispersant is added.

[0030] Preferably, in step S13, the paper weight is 50 g / m 2 , air permeability is 2000L / m 2 / s; in step S23, the paper weight is 65g / m 2 , air permeability is 1400L / m 2 / s; in step S33, the paper weight is 22g / m 2 , air permeability is 740L / m 2 / s.

[0031] Preferably, in step S14, the drying temperature is 130-150°C, and in steps S24 and S34, the drying temperature is 110-125°C.

[0032] Preferably, hot melt adhesive is used to bond the composite oil inlet surface all-synthetic material, the middle layer all-synthetic material, the oil outlet surface all-synthetic material and the polyester fiber spunbonded non-woven fabric, and the amount of hot melt adhesive sprayed between the oil inlet surface all-synthetic material and the middle layer all-synthetic material is 5-7g / m 2 The amount of hot melt adhesive sprayed between the middle layer of fully synthetic material and the oil-outlet surface fully synthetic material is 8-11g / m 2 The amount of hot melt adhesive sprayed between the oil-exiting surface fully synthetic material and the polyester fiber spunbond non-woven fabric is 13-15g / m 2 .

[0033] When hot melt adhesive is used to composite the oil inlet surface all-synthetic material, the middle layer all-synthetic material, the oil outlet surface all-synthetic material and polyester fiber spunbond non-woven fabric, the amount of hot melt adhesive sprayed between layers is increasing. This is because: 1) The amount of glue sprayed will affect the performance of the paper. If the amount of glue sprayed is too large, it will have an adverse effect on the dust holding capacity. Therefore, the amount of glue sprayed between the oil inlet surface and the middle layer is the least, and the amount of glue sprayed between the middle layer and the oil outlet surface is second; 2) The amount of glue sprayed is also related to the difficulty of bonding between layers. If the amount of glue sprayed is too small, it is easy to produce the risk of stratification. The oil outlet surface has high air permeability and is easy to combine, and the supporting polyester fiber spunbond non-woven fabric is not easy to stick together, so the amount of glue sprayed between the two is the largest.

[0034] Preferably, the polyester fiber spunbond nonwoven fabric has a burst resistance of >750 kPa and an air permeability of 1500-2200 L / m 2 / s, quantitative 120-150g / m 2 .

[0035] On the other hand, the present invention also provides a gradient fully synthetic engine oil filter material prepared by the above preparation method.

[0036] The filter material of the present invention adopts a gradient filtration design: the oil inlet surface is the first surface contacted before the oil is filtered, so the oil inlet surface design adopts 3D and 1.5D coarse polyester fibers, which can provide low initial resistance, and the service life ends when the pressure reaches the peak, so the lower the initial resistance, the longer its theoretical service life. The oil outlet surface is the last barrier for oil filtration, which provides the final accuracy guarantee, so the present invention adopts the current 0.3D high-precision polyester fiber, and adds 1.5D polyester fiber and core structure bicomponent polyester fiber to supplement the strength. If the filter material is composed of only the above two layers, it is impossible to form a step-by-step filtering effect. After some large particle impurities are not intercepted on the first layer of the oil inlet surface, they will quickly intercept the oil outlet surface. As the large particle impurities are quickly blocked on the surface and internal fibers of the last layer, the oil outlet surface of the last layer will cause huge resistance to oil transportation, causing the filter to eventually fail to alarm. Therefore, the present invention also sets an intermediate layer between the oil inlet surface and the oil outlet surface. The intermediate layer is a key layer for providing accuracy and dust holding. It can capture the escaped large particles again and filter out some small particles at the same time. When the three-layer structure is combined in sequence, impurities in the oil will be filtered out in order of particle size, allowing the paper to fully function before becoming ineffective.

[0037] In addition, the present invention compounds a polyester fiber spunbond nonwoven fabric on the oil outlet side, which has the following functions: 1) Providing strength: The polyester material mainly provides sufficient burst resistance and stiffness. It is located on the oil outlet side and does not participate in the improvement of performance indicators, nor can it have an adverse effect on the performance; 2) Meeting the aging resistance requirement: It only provides the strength requirement of the composite product alone, and should also have the requirement of resistance to hot oil aging.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] The present invention prepares engine oil filter paper through the all-synthetic fiber wet molding mixed papermaking integrated molding technology, which not only ensures the long-life engine filter use accuracy requirements, but also ensures the filter element's resistance to heat oil aging for more than 2000 hours, while avoiding the problem of poor moisture resistance and easy deformation of traditional wood pulp paper. At the same time, the present invention uses a gradient design to gradiently compound a three-layer structure with low quantitative, different precision and dirt holding capacity, and at the same time compounds a polyester material on the oil outlet surface. The origami and hot plate welding process can be directly performed, truly realizing a long-life, high-precision, low-resistance and high-efficiency all-synthetic engine filter material. The engine oil filter material prepared by the present invention can achieve a 20μm filtration efficiency of >90% (ISO4548-12 standard test), a dirt holding capacity of >180g / m²; the heat oil aging resistance meets >2000h, and the bursting resistance is >800kPa (150°C Great Wall lubricating oil). Specific implementation method

[0040] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments.

[0041] The core-sheath bicomponent polyester fiber used in the following examples and comparative examples has a low-temperature melting point of 110° C. and a high-temperature melting point of 220° C., and is manufactured by Teijin Limited of Japan.

[0042] Example 1

[0043] The preparation method of the gradient fully synthetic oil filter material of this embodiment comprises the following steps:

[0044] Preparation of S1 oil inlet surface fully synthetic material

[0045] S11 pulping: first disperse 13 parts of 1.5D polyester fiber and 50 parts of 3D polyester fiber through a hydraulic pulper for 5 minutes, then disperse 12 parts of skin-core structure two-component polyester fiber for 2 minutes, and finally disperse 1.5 parts of 10μm glass fiber for 8 minutes. The dispersion water is 100% clean water, the beating degree is greater than 40°SR, and the mass concentration of the fiber in the water is controlled to be 9% during the dispersion process; after dispersion, it is uniformly passed through a high-frequency deflaking machine without knife adjustment; then the pulp enters the pulp mixing tank and 0.1‰ dispersant is added;

[0046] S12 online forming: single-layer pulping and integrated papermaking through inclined wire paper machine;

[0047] S13 glue coating: using acrylic resin glue (glass transition temperature is 50℃) and PVA glue for dipping glue coating, the paper weight is 50g / m 2 , air permeability is 2000L / m 2 / s;

[0048] Among them, the glass transition temperature of acrylic resin glue is directly related to the flexibility of the molecular chain. If it is too high, the rigidity will be too great, affecting the flexibility of the paper sheet, and it will be prone to breakage during processing, resulting in a decrease in product performance; if it is too low, it will be too soft, and during processing, the stiffness will be too low, which will cause origami deformation and affect the appearance and performance.

[0049] S14 drying: drying the semi-finished product after gluing at 130°C to obtain the oil-injected fully synthetic material; the sheath-core structured two-component polyester fiber combined with surface gluing ensures the bursting strength of the fully synthetic fiber material;

[0050] Preparation of S2 middle layer fully synthetic material

[0051] S21 pulping: First, 61 parts of 0.67D polyester fiber are dispersed through a hydraulic pulper for 4 minutes, then 8 parts of bicomponent polyester fiber with skin-core structure are dispersed for 2 minutes, and finally 3 parts of 15μm glass fiber are dispersed for 10 minutes. The dispersion water is 100% clean water, and the beating degree is greater than 35°SR. During the dispersion process, the mass concentration of the fiber in the water is controlled to be 1.3%; after dispersion, it is uniformly passed through a high-frequency deflaking machine without knife adjustment; then the pulp enters the pulp mixing tank, and 0.1‰ anionic polyacrylamide APAM dispersant (Kemira Chemical Co., Ltd.) is added;

[0052] S22 online forming: single-layer pulping and integrated papermaking through inclined wire paper machine;

[0053] S23 glue coating: acrylic resin glue (glass transition temperature is 50℃) and PVA glue are used for surface coating, and the paper weight is 65g / m 2 , air permeability is 1400L / m 2 / s;

[0054] S24 drying: the semi-finished product after glue coating is dried at 110°C to obtain the middle layer full synthetic material. The sheath-core structured two-component polyester fiber combined with surface sizing ensures the bursting strength of the full synthetic fiber material;

[0055] Preparation of S3 oil outlet surface fully synthetic material

[0056] S31 pulping: first disperse 65 parts of 0.3D polyester fiber and 10 parts of 1.5D polyester fiber through a hydraulic pulper for 6 minutes, then disperse 5 parts of skin-core structure two-component polyester fiber for 1 minute, and finally disperse 5 parts of 1μm glass fiber for 15 minutes. The dispersion water is 100% clean water, the beating degree is greater than 50°SR, and the mass concentration of the fiber in the water is controlled to be 0.5% during the dispersion process; after dispersion, it is uniformly passed through a high-frequency deflaking machine without knife adjustment; then the pulp enters the pulp mixing tank, and 0.3‰ anionic polyacrylamide APAM dispersant is added;

[0057] S32 online forming: through the inclined wire paper machine single layer pulping, integrated papermaking forming;

[0058] S33 glue coating: Use acrylic resin glue (glass transition temperature is 50℃) for dipping glue coating, the paper weight is 22g / m 2 , air permeability is 740L / m 2 / s;

[0059] S34 Drying: Dry the semi-finished product after gluing at 110℃ to obtain the oil-surface fully synthetic material. The sheath-core structured two-component polyester fiber combined with surface sizing ensures the bursting strength of the fully synthetic fiber material.

[0060] The oil inlet surface synthetic material, the middle layer synthetic material and the oil outlet surface synthetic material are bonded by hot melt adhesive. After bonding, the oil outlet surface synthetic material is bonded with polyester fiber spunbond non-woven fabric (burst resistance> 750kPa, air permeability 1500 L / m 2 / s, basis weight is 120g / m 2 ); Among them, the amount of hot melt adhesive sprayed between the oil inlet surface full synthetic material and the middle layer full synthetic material is 5g / m 2 The amount of hot melt adhesive sprayed between the middle layer of fully synthetic material and the oil outlet surface fully synthetic material is 8g / m 2 The amount of hot melt adhesive sprayed between the oil-exiting surface fully synthetic material and the polyester fiber spunbond nonwoven fabric is 15g / m 2 .

[0061] Example 2

[0062] The preparation method of the gradient fully synthetic oil filter material of this embodiment comprises the following steps:

[0063] Preparation of S1 oil inlet surface fully synthetic material

[0064] S11 pulping: first disperse 19 parts of 1.5D polyester fiber and 62 parts of 3D polyester fiber through a hydraulic pulper for 7 minutes, then disperse 18 parts of skin-core structure two-component polyester fiber for 4 minutes, and finally disperse 3 parts of 10μm glass fiber for 11 minutes. The dispersion water is 100% clean water, the beating degree is greater than 40°SR, and the mass concentration of the fiber in the water is controlled to be 7% during the dispersion process; after dispersion, it is uniformly passed through a high-frequency deflaking machine without knife adjustment; then the slurry enters the slurry mixing tank and 0.1‰ dispersant is added;

[0065] S12 online forming: single-layer pulping and integrated papermaking through inclined wire paper machine;

[0066] S13 glue coating: using acrylic resin glue (glass transition temperature is 50℃) and PVA glue for dipping glue coating, the paper weight is 50g / m 2 , air permeability is 2000L / m 2 / s;

[0067] S14 drying: drying the semi-finished product after gluing at 150°C to obtain the oil-injected fully synthetic material; the sheath-core structured two-component polyester fiber combined with surface gluing ensures the bursting strength of the fully synthetic fiber material;

[0068] Preparation of S2 middle layer fully synthetic material

[0069] S21 pulping: First, 70 parts of 0.67D polyester fiber are dispersed through a hydraulic pulper for 6 minutes, then 15 parts of bicomponent polyester fiber with skin-core structure are dispersed for 4 minutes, and finally 5.5 parts of 15μm glass fiber are dispersed for 12 minutes. The dispersion water is 100% clean water, and the beating degree is greater than 35°SR. During the dispersion process, the mass concentration of the fiber in the water is controlled to be 1.5%; after dispersion, it is uniformly passed through a high-frequency deflaking machine without knife adjustment; then the pulp enters the pulp mixing tank and 0.1‰ dispersant is added;

[0070] S22 online forming: single-layer pulping and integrated papermaking through inclined wire paper machine;

[0071] S23 glue coating: acrylic resin glue (glass transition temperature is 50℃) and PVA glue are used for surface coating, and the paper weight is 65g / m 2 , air permeability is 1400L / m 2 / s;

[0072] S24 drying: drying the semi-finished product after gluing at 125°C to obtain the middle layer of fully synthetic material. The sheath-core structured two-component polyester fiber combined with surface gluing ensures the bursting strength of the fully synthetic fiber material.

[0073] Preparation of S3 oil outlet surface fully synthetic material

[0074] S31 pulping: First, 77 parts of 0.3D polyester fiber and 17 parts of 1.5D polyester fiber are dispersed by hydraulic pulper for 7 minutes, then 7 parts of skin-core structure two-component polyester fiber are dispersed for 3 minutes, and finally 7.5 parts of 1μm glass fiber are dispersed for 17 minutes. The dispersion water is 100% clean water, the beating degree is greater than 50°SR, and the mass concentration of the fiber in the water is controlled to be 1% during the dispersion process; after dispersion, it is uniformly passed through a high-frequency deflaking machine without knife adjustment; then the pulp enters the pulp mixing tank, and 0.3‰ anionic polyacrylamide APAM dispersant is added;

[0075] S32 online forming: through the inclined wire paper machine single layer pulping, integrated papermaking forming;

[0076] S33 glue coating: Use acrylic resin glue (glass transition temperature is 50℃) for dipping glue coating, the paper weight is 22g / m 2 , air permeability is 740L / m 2 / s;

[0077] S34 Drying: Dry the semi-finished product after gluing at 115°C to obtain the oil-surface fully synthetic material. The sheath-core structured two-component polyester fiber combined with surface sizing ensures the bursting strength of the fully synthetic fiber material.

[0078] The oil inlet surface synthetic material, the middle layer synthetic material and the oil outlet surface synthetic material are bonded by hot melt adhesive. After bonding, the oil outlet surface synthetic material is bonded with polyester fiber spunbond non-woven fabric (burst resistance> 750kPa, air permeability 2200 L / m 2 / s, quantitative 150g / m 2 ); Among them, the amount of hot melt adhesive sprayed between the oil inlet surface full synthetic material and the middle layer full synthetic material is 5g / m 2 The amount of hot melt adhesive sprayed between the middle layer of fully synthetic material and the oil outlet surface fully synthetic material is 8g / m 2 The amount of hot melt adhesive sprayed between the oil-exiting surface fully synthetic material and the polyester fiber spunbond nonwoven fabric is 15g / m 2 .

[0079] Example 3

[0080] The preparation method of the gradient fully synthetic oil filter material of this embodiment comprises the following steps:

[0081] Preparation of S1 oil inlet surface fully synthetic material

[0082] S11 pulping: first disperse 15 parts of 1.5D polyester fiber and 56 parts of 3D polyester fiber through a hydraulic pulper for 6 minutes, then disperse 15 parts of skin-core structure two-component polyester fiber for 3 minutes, and finally disperse 2.2 parts of 10μm glass fiber for 10 minutes. The dispersion water is 100% clean water, the beating degree is greater than 40°SR, and the mass concentration of the fiber in the water is controlled to be 12% during the dispersion process; after dispersion, it is uniformly passed through a high-frequency deflaking machine without knife adjustment; then the pulp enters the pulp mixing tank and 0.1‰ dispersant is added;

[0083] S12 online forming: single-layer pulping and integrated papermaking through inclined wire paper machine;

[0084] S13 glue coating: using acrylic resin glue (glass transition temperature is 50℃) and PVA glue for dipping glue coating, the paper weight is 50g / m 2 , air permeability is 2000L / m 2 / s;

[0085] S14 drying: drying the semi-finished product after gluing at 140°C to obtain the oil-injected fully synthetic material; the sheath-core structured bicomponent polyester fiber combined with surface gluing ensures the bursting strength of the fully synthetic fiber material;

[0086] Preparation of S2 middle layer fully synthetic material

[0087] S21 pulping: first disperse 65 parts of 0.67D polyester fiber through a hydraulic pulper for 4 minutes, then disperse 11 parts of bicomponent polyester fiber with skin-core structure for 2 minutes, and finally disperse 4 parts of 15μm glass fiber for 10 minutes. The dispersion water is 100% clean water, the beating degree is greater than 35°SR, and the mass concentration of the fiber in the water is controlled to be 1.4% during the dispersion process; after dispersion, it is uniformly passed through a high-frequency deflaking machine without knife adjustment; then the slurry enters the slurry mixing tank and 0.1‰ dispersant is added;

[0088] S22 online forming: single-layer pulping and integrated papermaking through inclined wire paper machine;

[0089] S23 glue coating: acrylic resin glue (glass transition temperature is 50℃) and PVA glue are used for surface coating, and the paper weight is 65g / m 2 , air permeability is 1400L / m 2 / s;

[0090] S24 drying: the semi-finished product after glue coating is dried at 115°C to obtain the middle layer full synthetic material. The sheath-core structured two-component polyester fiber combined with surface sizing ensures the bursting strength of the full synthetic fiber material;

[0091] Preparation of S3 oil outlet surface fully synthetic material

[0092] S31 pulping: First, 71 parts of 0.3D polyester fiber and 13 parts of 1.5D polyester fiber are dispersed by hydraulic pulper for 6 minutes, then 6 parts of skin-core structure two-component polyester fiber are dispersed for 2 minutes, and finally 6.2 parts of 1μm glass fiber are dispersed for 16 minutes. The dispersion water is 100% clean water, the beating degree is greater than 50°SR, and the mass concentration of the fiber in the water is controlled to be 0.5% during the dispersion process; after dispersion, it is uniformly passed through a high-frequency deflaking machine without knife adjustment; then the pulp enters the pulp mixing tank, and 0.3‰ anionic polyacrylamide APAM dispersant is added;

[0093] S32 online forming: through the inclined wire paper machine single layer pulping, integrated papermaking forming;

[0094] S33 glue coating: Use acrylic resin glue (glass transition temperature is 50℃) for dipping glue coating, the paper weight is 22g / m 2 , air permeability is 740L / m 2 / s;

[0095] S34 Drying: Dry the semi-finished product after gluing at 125℃ to obtain the oil-surface fully synthetic material. The sheath-core structured two-component polyester fiber combined with surface sizing ensures the bursting strength of the fully synthetic fiber material.

[0096] The oil inlet surface synthetic material, the middle layer synthetic material and the oil outlet surface synthetic material are bonded by hot melt adhesive. After bonding, the oil outlet surface synthetic material is bonded with polyester fiber spunbond non-woven fabric (burst resistance> 750kPa, air permeability 1800 L / m 2 / s, quantitative 135g / m 2 ); Among them, the amount of hot melt adhesive sprayed between the oil inlet surface full synthetic material and the middle layer full synthetic material is 5g / m 2 The amount of hot melt adhesive sprayed between the middle layer of fully synthetic material and the oil outlet surface fully synthetic material is 8g / m 2 The amount of hot melt adhesive sprayed between the oil-exiting surface fully synthetic material and the polyester fiber spunbond nonwoven fabric is 15g / m 2 .

[0097] Comparative Example 1

[0098] The difference from Example 1 is that the filter material does not include a fully synthetic material on the oil inlet surface.

[0099] Comparative Example 2

[0100] The difference from Example 1 is that the filter material does not include an intermediate layer of fully synthetic material.

[0101] Comparative Example 3

[0102] The difference from Example 1 is that the filter material does not include a fully synthetic material on the oil outlet surface.

[0103] Comparative Example 4

[0104] The difference from Example 1 is that the filter material does not include polyester fiber spunbonded nonwoven fabric.

[0105] Comparative Example 5

[0106] The difference from Example 1 is that the compounding sequence of the filter material is adjusted, and the oil outlet surface fully synthetic material, the middle layer fully synthetic material, the oil inlet surface fully synthetic material and the polyester fiber spunbonded non-woven fabric are compounded together in sequence.

[0107] Comparative Example 6

[0108] The difference from Example 1 is that the compounding order of the filter material is adjusted, and the middle layer full synthetic material, the oil inlet surface full synthetic material, the oil outlet surface full synthetic material and the polyester fiber spunbonded non-woven fabric are compounded together in sequence.

[0109] Comparative Example 7

[0110] The difference from Example 1 is that the amount of hot melt adhesive sprayed between the oil inlet surface fully synthetic material and the middle layer fully synthetic material is 8g / m 2The amount of hot melt adhesive sprayed between the middle layer of fully synthetic material and the oil-outlet surface fully synthetic material is 15g / m 2 The amount of hot melt adhesive sprayed between the oil-exiting surface fully synthetic material and the polyester fiber spunbond nonwoven fabric is 5g / m 2 .

[0111] The filter materials of Examples 1-3 and Comparative Examples 1-7 were tested for performance, and the test results are shown in Table 1:

[0112] Table 1

[0113]

[0114] As can be seen from Table 1, compared with Example 1, the dust holding capacity of Comparative Example 1 decreases. This is because the oil inlet surface mainly forms a gradient filtration with the middle layer, and it has high air permeability and high dust holding capacity. Therefore, after removing the oil inlet surface, large particles of impurities will accelerate the aggregation and cause the service life to decrease. The filtration efficiency and dust holding capacity of Comparative Example 2 decrease. This is because the middle layer forms a gradient filtration with the oil outlet surface and the oil inlet surface, and also plays a certain role in improving the filtration efficiency. The filtration efficiency and dust holding capacity of Comparative Example 3 decrease. This is because the oil outlet surface forms a gradient filtration with the oil inlet surface and the middle layer, and mainly plays a role in high-precision filtration. The aging resistance and burst resistance of Comparative Example 4 decrease. This is because the polyester layer provides most of the strength. The dust holding capacity of Comparative Example 5 decreases. This is because the high-precision filtration layer becomes the oil inlet surface, destroying the gradient structure. The dust holding capacity of Comparative Example 6 decreases. This is because the middle layer becomes the oil inlet surface, destroying the gradient structure. The aging resistance of Comparative Example 7 decreases. This is because the low amount of viscose causes partial delamination during the test.

Claims

1. A method for preparing a gradient fully synthetic oil filter material, characterized in that: The following steps are involved: Preparation of S1 oil inlet surface fully synthetic material S11 pulping: first disperse 1.5D polyester fiber and 3D polyester fiber, then disperse the skin-core structure two-component polyester fiber, and finally disperse the glass fiber; S12 Internet access forming; S13 Gluing: Use acrylic resin glue and PVA glue for dipping glue; S14 drying: drying the semi-finished product after glue coating to obtain the oil-filled fully synthetic material; Preparation of S2 middle layer fully synthetic material S21 pulping: first disperse 67D polyester fiber, then disperse the skin-core structure two-component polyester fiber, and finally disperse the glass fiber; S22 online forming: single-layer pulping and integrated papermaking through inclined wire paper machine; S23 Gluing: Use acrylic resin glue and PVA glue for surface coating; S24 drying: drying the semi-finished product after gluing to obtain the middle layer fully synthetic material; Preparation of S3 oil outlet surface fully synthetic material S31 pulping: first disperse 0.3D polyester fiber and 1.5D polyester fiber, then disperse the skin-core structure two-component polyester fiber, and finally disperse the glass fiber; S32 online forming: single-layer pulping and integrated papermaking through inclined wire paper machine; S33 Gluing: Use acrylic resin glue for dipping; S34 Drying: Drying the semi-finished product after gluing to obtain the oil surface full synthetic material; Among them, the glass transition temperature of acrylic resin glue is 50°C; Compounding the oil inlet surface all-synthetic material, the middle layer all-synthetic material and the oil outlet surface all-synthetic material, after compounding, compounding the polyester fiber spunbond non-woven fabric on the oil outlet surface all-synthetic material; Hot melt adhesive is used to bond the composite oil inlet surface all-synthetic material, the middle layer all-synthetic material, the oil outlet surface all-synthetic material and polyester fiber spunbond non-woven fabric. The amount of hot melt adhesive sprayed between the oil inlet surface all-synthetic material and the middle layer all-synthetic material is 5-7g / m 2 The amount of hot melt adhesive sprayed between the middle layer of fully synthetic material and the oil-outlet surface fully synthetic material is 8-11g / m 2 The amount of hot melt adhesive sprayed between the oil-exiting surface of the fully synthetic material and the polyester fiber spunbond non-woven fabric is 13-15g / m 2 ; In step S11, pulping includes the following raw materials in parts by weight: 50-62 parts of 3D polyester fiber, 12-19 parts of 1.5D polyester fiber, 12-18 parts of bicomponent polyester fiber with a core-skin structure and 1.5-3 parts of glass fiber, and the beating degree is greater than 40°SR; in step S21, pulping includes the following raw materials in parts by weight: 61-70 parts of 67D polyester fiber, 8-15 parts of bicomponent polyester fiber with a core-skin structure and 3-5.5 parts of glass fiber, and the beating degree is greater than 35°SR; in step S31, pulping includes the following raw materials in parts by weight: 65-77 parts of 0.3D polyester fiber, 10-17 parts of 1.5D polyester fiber, 5-7 parts of bicomponent polyester fiber with a core-skin structure and 5-7.5 parts of glass fiber, and the beating degree is greater than 50°SR; In step S11, the dispersion time of 1.5D polyester fiber and 3D polyester fiber is 5-7min, the dispersion time of sheath-core bicomponent polyester fiber is 2-4min, and the dispersion time of glass fiber is 8-11min; in step 21, the dispersion time of 67D polyester fiber is 4-6min, the dispersion time of sheath-core bicomponent polyester fiber is 2-4min, and the dispersion time of glass fiber is 10-12min; in step S31, the dispersion time of 0.3D polyester fiber and 1.5D polyester fiber is 6-7min, the dispersion time of sheath-core bicomponent polyester fiber is 1-3min, and the dispersion time of glass fiber is 15-17min.

2. The method for preparing a gradient fully synthetic oil filter material according to claim 1, characterized in that: In steps S11, S21 and S31, the dispersion process is carried out in a hydraulic pulper; in step S11, the mass concentration of the fiber in water is 7-12%, in step S21, the mass concentration of the fiber in water is 1.2-1.5%, and in step S31, the mass concentration of the fiber in water is 0.5-1%.

3. The method for preparing a gradient fully synthetic oil filter material according to claim 1, characterized in that: In steps S11, S21 and S31, after dispersion, the slurry is uniformly passed through a high-frequency deflaking machine without knife adjustment; then the slurry enters a slurry mixing tank and a dispersant is added, wherein in steps S11 and S21, 0.1‰ of dispersant is added, and in step S31, 0.3‰ of dispersant is added.

4. The method for preparing a gradient fully synthetic oil filter material according to claim 1, characterized in that: In step S13, the paper weight is 50g / m 2 , air permeability is 2000L / m 2 / s; in step S23, the paper weight is 65g / m 2 , air permeability is 1400L / m 2 / s; in step S33, the paper weight is 22g / m 2 , air permeability is 740L / m 2 / s.

5. The method for preparing a gradient fully synthetic oil filter material according to claim 1, characterized in that: In step S14, the drying temperature is 130-150°C, and in steps S24 and S34, the drying temperature is 110-125°C.

6. The method for preparing a gradient fully synthetic oil filter material according to claim 1, characterized in that: The bursting strength of polyester fiber spunbond nonwoven fabric is >750kPa and the air permeability is 1500-2200L / m 2 / s, quantitative 120-150g / m 2 .

7. A gradient fully synthetic engine oil filter material prepared by the preparation method according to any one of claims 1 to 6.